Beyond the resistive index: value of color-coded duplex sonography parameters in kidney transplantation - Konzett, Katharina; Neururer, Sabrina; Tiefenthaler, Martin (Frontiers in Nephrology, 2026)
Sonography is a key method in examining kidney transplants. Recent reports on the limited diagnostic value of an elevated resistive index (RI) in detecting rejection have cast doubt on the overall utility of color-coded duplex sonography (CCDS). This study evaluated additional CCDS parameters – percentage of vascularization (POV) and periphery vessel distance (PVD) – and investigated their association with histopathologic findings in allograft dysfunction. In a retrospective single-center study, 350 kidney transplant biopsies performed between 2013 and 2022 were analyzed. Standardized sonographic evaluation, including POV, PVD, and RI, was conducted at biopsy request. Histopathologic lesions were scored according to Banff criteria. Multivariable logistic regression identified independent predictors of abnormal CCDS parameters. Recipient age, severe tubular atrophy (ct), and arterial intimal fibrosis (cv) were independent negative predictors of POV > 50%. PVD ≥ 0.25 cm was associated with recipient age and moderate tubular atrophy (ct). RI showed no association with histopathologic lesions. These findings identify POV and PVD as non-invasive markers of chronic injury in kidney allografts, highlighting their potential adjunctive role in detecting parenchymal damage. As such, CCDS may support – but not replace – biopsy, which remains essential for establishing a definitive diagnosis in graft dysfunction.